2007
DOI: 10.1302/0301-620x.89b6.18712
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the natural history of massive lumbar disc herniation

Abstract: We have treated 15 patients with massive lumbar disc herniations non-operatively. Repeat MR scanning after a mean 24 months (5 to 56) showed a dramatic resolution of the herniation in 14 patients. No patient developed a cauda equina syndrome. We suggest that this condition may be more benign than previously thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 18 publications
2
62
0
1
Order By: Relevance
“…These results are similar to the recent studies done using MRI; Cribb et al 15) reported that, by following up on 15 cases with more than 50% spinal canal encroachments for 24 months, in 14 of the 15 cases, improvement of clinical symptoms was shown without surgery, and reported that on average 80% reduction in size was shown, hence suggested that a careful consideration needs to be given regarding surgery due to potential surgical complications. In addition, Benson et al 16) by following up on 37 cases with more than 50% spinal canal encroachments for 23 months, reported that 83% satisfactory results were obtained, while only 4 cases required surgery.…”
Section: ) Agesupporting
confidence: 89%
“…These results are similar to the recent studies done using MRI; Cribb et al 15) reported that, by following up on 15 cases with more than 50% spinal canal encroachments for 24 months, in 14 of the 15 cases, improvement of clinical symptoms was shown without surgery, and reported that on average 80% reduction in size was shown, hence suggested that a careful consideration needs to be given regarding surgery due to potential surgical complications. In addition, Benson et al 16) by following up on 37 cases with more than 50% spinal canal encroachments for 23 months, reported that 83% satisfactory results were obtained, while only 4 cases required surgery.…”
Section: ) Agesupporting
confidence: 89%
“…45 Greater than 70% of patients with radiculopathy will recover within 6 months, 46,47 and a similar proportion will experience resorption of a herniated disk within 1 year of presentation. 48,49 Another rationale for the use of ESI is that the evidence in support of the procedure is more robust (ie, more clinical trials showing benefit), and the risk-benefit ratio more favorable, compared with other treatments. Among randomized clinical trials evaluating surgery for neuropathic LBP and neck pain irrespective of etiology, most demonstrate temporary (ie, 6 months) but not long-term benefit.…”
Section: Efficacy and Type Of Injectionmentioning
confidence: 99%
“…Large LDH has been reported to have a greater tendency to resolve in clinical and pathomorphological evolutions 7910111213. The ‘massive’ LDH, which was defined in previous studies as the disc material occupying >50% of the spinal canal on axial magnetic resonance (MR) images, showed a successful outcome with nonoperative treatment 1415. Therefore, operative treatment of massive LDH can be deferred unless significant neurological symptoms are observed.…”
Section: Introductionmentioning
confidence: 99%